Smart factories for industry 5.0 transformation - Nidhya, R.; Kumar, Manish; Karthik, S.; Anand, Rishabh; Balamurugan, S. (Industry 5.0 transformation applications., 2025)
This book serves as a comprehensive guide, exploring the technologies, design principles, and operational strategies behind smart factories. In an era where industrial expertise meets digital innovation, the "smart factory" symbolizes a new wave of efficiency and advancement. Industry 5.0 represents a paradigm shift, integrating technologies like robotics, AI, IoT, and big data to enhance human-machine collaboration while improving sustainability, quality, and efficiency. It offers businesses valuable insights and real-world examples to navigate the opportunities and challenges of Industry 5.0. This book goes beyond technical explanations to examine the broader impact of the Industry 5.0 revolution on global supply chains and socioeconomic change, encouraging readers to view technology as a force for good. It appeals to all levels of expertise, providing valuable insights for experienced professionals while serving as an introduction for newcomers. Above all, it invites readers to embrace the collaborative spirit and creativity of Industry 5.0, joining in the effort to build the smart factories that will drive the future of innovation. Audience Researchers, industry engineers, and technologists working in artificial intelligence and Industry 5.0 application areas such as healthcare, transportation, manufacturing, and more.